A Positive Association between T. gondii Seropositivity and Obesity - Reeves, Gloria M.; Postolache, Teodor T.; Mazaheri, Sara; Snitker, Soren; Langenberg, Patricia; Giegling, Ina; Hartmann, Annette; Konte, Bettina; Friedl, Marion; Okusaga, Olaoluwa; Groer, Maureen; Mangee, Harald; et al. (Frontiers in Public Health, 2013)
Obesity is a global public health problem that is linked with morbidity, mortality and functional limitations and has limited options for sustained interventions. Novel targets for prevention and intervention require further research into the pathogenesis of obesity. An emerging field of research has investigated the association of infections and environmental pathogens with obesity, and inflammatory mechanisms that may mediate obesity risk. In this study, we estimate the possible association between Toxoplasma gondii (T. gondii) infection and obesity in a sample of 999 adults that have been carefully screened for mental illness. Individuals are screened for mental illness because of the association between positive serology to T. gondii and various forms of serious mental illness that have a strong association with obesity. In our sample, individuals with positive T. gondii serology were twice the odds of being obese compared to seronegative individuals (p = .01). Further, individuals who were obese had significant higher T. gondii IgG titers compared to individuals who were non-obese. Latent T. gondii infection is very common worldwide, so potential public health interventions related to this parasite can have a high impact on associated health concerns.